Estimation of human capital in the strategic budgeting system - Kamenska, O.; Vesela, N. (Економічний вісник Донбасу, 2016)
This paper proposes a method for calculating assessment of employees working abilities in the system of strategic budgeting of an industrial enterprise, which is based on the synthesis of components of the qualification indexes of employees and which, in contrast to the existing ones, takes into account the relation between the strategic objectives and cost items in the budget of the enterprise. This method allows disclosure of the potential value of human capital and the compliance of its quality with strategic priorities of the company.